Studi eksperimen rumah pengering ultra-violet (solar dryer) sistem hibrid tungku biomassa melalui variasi kecepatan aliran udara panas - Verdy A. Koehuan; Margaretha Kewa Unarajan; Defmit B.N. Riwu; Muhamad Jafri (Universitas Muhammadiyah Metro, 2023)
The ultra-violet dryer integrated with the biomass furnace is a drying method with a forced mechanism. In this study, an experimental study was carried out. The drying process of porang tubers uses a hybrid system ultra violet plastic dryer (UV solar dryer) through varying the speed of the inlet air to obtain efficient drying results and porang tuber products. The results showed that the final moisture content of porang tubers after drying per day for each variation of air speed obtained the lowest value of 10.50%bb with the highest drying rate of 0.3373 kg/hour from the assumption of an initial moisture content of 70%bb, which occurs in variations airspeed of 1.8 m/s. while the speed is 1.3 m/s with the lowest drying rate of 0.330 kg/hour with a final moisture content of 11.74%.bb) Drying efficiency for variations in the speed of hot air flow into the hot air duct of the biomass furnace shows the highest value at a speed of 1.3 m/s of 16.76% with the lowest specific energy consumption (KES) of 51975.7 kJ/kg.